Budget implementation in a risky environment: evidence from the Indonesian public sector. Issue 2 (7th May 2019) - Rakhman, Fuad
Abstract : Purpose: The purpose of this paper is to investigate factors affecting budget implementation among local governments in Indonesia, where rules are relatively strict and risks of facing corruption charges are high. Design/methodology/approach: This study employs regression analyses using a sample of 1, 151 local government-years. Findings: This study finds that the level of budget implementation is affected by the leadership factors (i.e. mayors' term, tenure and age) and the proportion of capital expenditures. The level of budget implementation is relatively lower when the mayor is in the second term, is in the early years of the five-year tenure and is over 60 years old. Higher proportion of capital expenditures also reduces the level of budget implementation. Originality/value: This study contributes to the literature by presenting empirical evidence as to what factors explain the variations in the level of budget implementation among local governments especially under strict rules and a risky environment.